1997
DOI: 10.1002/(sici)1096-911x(199712)29:6<560::aid-mpo7>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy for spinal cord astrocytoma

Abstract: Background The optimal management of spinal cord astrocytomas remains to be defined, as aggressive surgery and radiotherapy are associated with a high risk of morbidity. The value of chemotherapy has not been assessed. Procedure The patient in the present report harbored an infiltrating spinal cord tumor causing paraplegia. A limited biopsy showed a grade II astrocytoma. Following biopsy, the patient received sequential chemotherapy with vincristine and carboplatin. Results Full neurological recovery and compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Salvage chemotherapy with oral etoposide in a small cohort of patients with recurrent medically and surgically refractory ependymomas has been shown to have a modest activity in maintaining stable disease [2]. There is also anecdotal evidence of a grade II astrocytoma in a child responding to chemotherapy alone [1], but this result is not duplicated elsewhere in the literature and palliative care is often a more appropriate option.…”
Section: Discussionmentioning
confidence: 99%
“…Salvage chemotherapy with oral etoposide in a small cohort of patients with recurrent medically and surgically refractory ependymomas has been shown to have a modest activity in maintaining stable disease [2]. There is also anecdotal evidence of a grade II astrocytoma in a child responding to chemotherapy alone [1], but this result is not duplicated elsewhere in the literature and palliative care is often a more appropriate option.…”
Section: Discussionmentioning
confidence: 99%
“…The role of radiotherapy in pediatric patients with intramedullary spinal cord low-grade gliomas remains a vexed issue because the data that is available does not have suf cient statistical power (Bouffet et al, 1997;DeSousa et al, 1979;Lowis et al, 1998;Reimer and Onofrio, 1985). The threshold for spinal cord toxicity is approximately 45 to 50 Gy (Bouffet et al, 1997;Hopewell, 1998;Linstadt et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The threshold for spinal cord toxicity is approximately 45 to 50 Gy (Bouffet et al, 1997;Hopewell, 1998;Linstadt et al, 1989). This is based on the concept that the still developing spinal cords of children have a tolerance that is 10% to 15% lower than in adults, resulting in a greater susceptibility to radiationinduced myelopathy (Constantini et al, 1996;Reimer and Onofrio, 1985;Schultheiss et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are only a few case reports of this treatment modality in intramedullary astrocytoma. Bouffet et al (1997) reported the case of a 30-year-old woman with a grade II spinal cord astrocytoma treated first with carboplatin, who entered full neurological and radiological remission. The result was promising despite the short follow-up.…”
Section: Discussionmentioning
confidence: 99%